Bacteriophages in Health and Disease - Hyman, Paul (CABI, 2014)
If all things have to have a beginning, then the beginning of this monograph, arguably, can be traced to the 1980s in the laboratory of Harris Bernstein (Department of Microbiology and Immunology, University of Arizona). That was the lab that both of us joined to do our Ph.D. research and where we met. Though we worked on separate projects, both involved phages and this led to many discussions. Thus the team began. At er graduating we went our separate ways. While S.T.A. dabbled in what eventually would be all things phage ecological, P.H. followed a much more molecular, then medical, then applied route, but ultimately returned to phage biology and what would be a series of collaboration with S.T.A., starting in 2001. The story of how this monograph came to be is slightly more complicated, however. S.T.A. – at the time at the beginning of his career at the Ohio State University, in 1995 – founded what would become the Bacteriophage Ecology Group. His management of the associated web site (phage.org, though see also archaealviruses.org) began to lead to chapter invitations in the early 2000s, resulting in part in his contributing to the editing of Rich Calendar’s The Bacteriophages 2/e, which was published in 2006. Very soon at er S.T.A.’s contribution to that monograph ended he was invited to edit a monograph on phage ecology, which would become the 2008 Bacteriophage Ecology (Cambridge University Press), included in which was a chapter we coauthored. Meanwhile, speculators brought down the world’s economy, hit ing academic publishers quite hard. The series that Bacteriophage Ecology had been a part of, Advances in Molecular and Cellular Microbiology, was sold to CABI Press (cabi.org), ‘a not-for-proﬁ t international organization that improves people’s lives by providing information and applying scientiﬁ c expertise to solve problems in agriculture and the environment.’ It was 100% their idea to do the current monograph and, based on his experience with the Bacteriophage Ecology volume, S.T.A. was recruited to edit it. S.T.A., though, was busy at the time, pulling together an edited volume on phage therapy (see Current Pharmaceutical Biotechnology, volume 11, issue 1), so recruited P.H. to join in on yet another collaboration. We developed a formal proposal including recruiting the authors of the many chapters found herein and the result is this monograph.